Lower-limb mechanics during the support phase of maximum-velocity sprint running - Bezodis, I. N.; Kerwin, D. G.; Salo, A. I. T. (Medicine & Science in Sports & Exercise, 2008)
Introduction: The forces produced by an athlete during the support phase of a sprint run are a vital determinant of the outcome of the performance. The purpose of this study was to improve the understanding of sprint technique in well-trained sprinters through the comprehensive analysis of joint kinetics during the support phase of a maximum-velocity sprint.